Antioxidant Properties of Cocoa Pod Husk Powder as Affected by Slicing and Oven-Drying - Azizah, Siti Nur; Febrianto, Noor Ariefandie; Sukardi, . (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Cocoa pod husk (CPH) represents an underutilized by-product of the cocoa commodity. Their utilization has been hindered by their bulkiness, high processingcost and their limited use as food ingredients. A functional and effective processing method is needed to fully optimize this commodity. This study evaluated theeffect of slicing and oven-drying treatment on the antioxidant properties of cocoa pod husk powder. A response surface methodology (RSM) was used to contour-plot the drying rate, and antioxidative properties of CPH as the effect of different treatments. A central composited design consisting of three levels of drying temperature (55, 65, and 75°C) and three levels of slice thickness (1, 2, and 3 mm) was used in triplicate. The results showed that this technique could produce CPH powder with a light-brown appearance. Drying at 51-55°C with 1-3 mm thickness produced CPH powder with high antioxidative properties. A quick-drying method with a maximum temperature of 65°C and slice thickness of 0.6 mm could also produce CPH powder with high antioxidative properties. Principal component analysis showed that 65°C might be the maximum drying temperature limit to obtain CPH powder with high phenolic. Drying method used in this study enhanced the potential of CPH powder for food ingredient due to its good appearance and high phenolics characteristic.